Transformasi Sistem Pembayaran Digital: Analisis Implementasi dan Dampak Penggunaan Virtual Account pada Sektor Perbankan dan Pendidikan - Farhan Adi; Risqi Tirta Diroska; Ida Ayu Nuh Kartini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The development of digital technology has changed the way financial transactions through the use of virtual accounts (VA) as an automatic and accurate payment method. This study aims to analyze the working mechanism, advantages, and implementation of VA based on national and international literature. The method used is a literature study by studying relevant journals. The results show that the use of VA significantly improves time efficiency, record-keeping accuracy, and transaction security by reducing the risk of manual errors. The implementation of VA has proven to be effective in the education and banking sectors in supporting the digitalization of administration.